Serum Amyloid A (SAA) and its interaction with high-density lipoprotein cholesterol (HDL-C): a comprehensive review - Moissl-Blanke, Angela P.; Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; Siekmeier, Rüdiger; Dürschmied, Daniel; März, Winfried; Kleber, Marcus E. (International journal of molecular sciences, 2025)
Serum Amyloid A (SAA) is an acute-phase apolipoprotein that acts as both a sensitive biomarker of systemic inflammation and an active modulator of lip...